A Critical Appraisal of the Evidence Supporting the Factor Structure of Extant Coping Instruments. Issue 3 (September 2022) - Gugiu, P. Cristian; Drew, Damon; Polek, Ela
This paper evaluated the evidence supporting the factor structure of extant coping instruments based on modern psychometric standards. Our literature search identified nine coping instruments that are routinely used to measure coping strategies in adult populations. While nearly 10 thousand papers have been published using these instruments, only 39 studies have investigated their psychometric validity. Our findings revealed that the majority of these studies did not follow current psychometric recommendations for establishing internal validity in part because they did not account for the ordinal nature of the data. Further, studies employing exploratory factor analysis used methods for identifying the number of factors to retain that have been found to have a low accuracy in a simulation study while those employing confirmatory factor analysis reported model fit statistics that did not meet widely accepted benchmarks. Hence, conflicting results were found within and across the nine coping instruments. Recommendations are made for improving future validation studies.